Analysis of forces and surface roughness in magnetic abrasive finishing with a ball-end tool. (2013) - Sathua, Chandra Sekhar; Jain, V.K.; Ramkumar, J.; Sidpara, Ajay
Magnetic Abrasive Finishing (MAF) is an efficient finishing technique because of the self-adaptability of the magnetic abrasive brush in accordance with the shape of the product. To make this MAF process more capable, a new ball-ended tool has been developed to finish a non-magnetic material (brass) of semi-cylindrical shapes. Knowledge of forces acting during the finishing operation is important, as it gives an insight to the mechanism of material removal and the surface generation during finishing. A dynamometer and virtual instrumentation have been used to study and analyse the forces acting on the workpiece during the finishing operation. These forces can well explain the mechanism of surface generation, and variation in surface roughness with the parameters selected for the present research work.